HELICOBACTER PYLORI ASSOCIATED WITH VASCULITIS CUTANEUS AND WITH THE PRESENCE OF ULCEROUS LESIONS - F Arocha Sandoval; R Roa; K Parra Quevedo (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2001)
A 16 year old Caucasian female patient from the city of Maracaibo who became ill, in November of 1999, presenting common eritomatosic lesions in the left ankle increasing in size and ulcerated, later presented similar lesions and characteristics in the right ankle, and in February of 2000 visited a dermatologist who indicated a treatment with topical and oral steroids. A biopsy was performed of the ulcerous lesion reporting vasculitis with necrosis fibrinoide. The patient does not respond to treatment and the treatment is stopped. A test of immune serological gave negative results. The antibodies IgM anti-Helicobacter pylori however are positive, indicating treatment with Metronidazol and Claritromicina which is realized for a week. Results are positive with the disappearance of the ulcerous lesions. The relationship between H. Pylori and skin lesions in patients has been reported by other authors. Neri and Col associated with prurogo nodularis while Mozrzymas and Col found antibodies against H. Pyloris in patients with Henoch Scholein Purple. In both cases there was improvement with antibiotic treatment. In conclusion, H. pylori should be discarded as the agent responsible for the immunology phenomena such as vasculitis when we find immunology illnesses without apparent explanation.